PEMIKIRAN ETIKA MUTAHHARI - Amin, Muahammad (LPPM IAIN Parepare, 2017)
Murtadh? Muthahhar? is a philosopher, sufi of contemporary syi?ah, and one of Iranian ideologist of Islam revolution. His study focuses on the fiqh which imparts more loves to the philosophy, tasawuf, and theology. The point of his view was that human deed could be distinguished between the natural and moral (akhl?q?) deed. The natural was the deed that is not laudable. It is also implemented by animals. Then, the akhl?q? was the deed that is laudable in which it is like with the attempt. Human recognizes great being which is unmeasurable with the materials. It rises from the maujud having two sides which are in metaphysic and material and have spirit and body. Within Worship Theory, Murtadh? Muthahhar? classified that morals will not have the meaning if it is not with the recognition of God (ma?rifat All?h). Furthermore, tauh?d in his view is the root of the moral of faithful people in which it will not be lifted by the power at all.